2017
DOI: 10.1371/journal.pone.0185191
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the CPAP-treated patient population in Catalonia

Abstract: There are different phenotypes of obstructive sleep apnoea (OSA), many of which have not been characterised. Identification of these different phenotypes is important in defining prognosis and guiding the therapeutic strategy. The aim of this study was to characterise the entire population of continuous positive airway pressure (CPAP)-treated patients in Catalonia and identify specific patient profiles using cluster analysis.A total of 72,217 CPAP-treated patients who contacted the Catalan Health System (CatSa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…Our findings are of clinical relevance because they underline that asthmatic patients are under‐referred for sleep studies, despite the existing evidence of a high prevalence of OSA in asthma (Kong et al., ) and the positive effects of OSA treatment on asthma control (Kauppi et al., ; Wang et al., ). The prevalence of physician‐diagnosed asthma in our cohort was of the same order of magnitude as the prevalence rate of asthma recently found in CPAP‐treated patients (Turino et al., ). Certain phenotypes of asthma patients (i.e.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings are of clinical relevance because they underline that asthmatic patients are under‐referred for sleep studies, despite the existing evidence of a high prevalence of OSA in asthma (Kong et al., ) and the positive effects of OSA treatment on asthma control (Kauppi et al., ; Wang et al., ). The prevalence of physician‐diagnosed asthma in our cohort was of the same order of magnitude as the prevalence rate of asthma recently found in CPAP‐treated patients (Turino et al., ). Certain phenotypes of asthma patients (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…In the study by Greenberg‐Dotan and coworkers, the prevalence of asthma was 10.0% in OSA patients and 5.1% in controls, and significantly higher in women than in men (Greenberg‐Dotan et al., ). On the other hand, in a large cohort of OSA patients treated with CPAP, the asthmatic cluster accounted for only 5.8% of the cohort (Turino et al., ). Thus, data on the prevalence of asthma in OSA patients are variable, possibly reflecting differences in the studied samples and/or in the methods used to assess asthma and diagnose sleep apnea.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, in order to determine patterns of pathology in CMC population, diagnoses related to each individual, coded through CCS, were used. Homogeneous groups of patients with similar diseases were identified in CMC population via K-means cluster analysis using the Jaccard similarity index 22 , as in similar studies 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, these results are based on well‐managed cohorts and national or multinational registries mainly from academic environments with relatively small data sets (up to 18 000 OSA subjects) that do not necessarily reflect the wide range of real‐life situations and diverse clinical care pathways. A cluster analysis of Big Data acquired at a general population level showed that in an entire group of 72 217 CPAP‐treated patients certain OSA patient characteristics such as ‘neoplastic’ or ‘elderly with cardiac disease’ were associated with the highest mortality rates and healthcare resource use …”
Section: Opportunities Of Big Data In Understanding Sleep Breathing Dmentioning
confidence: 99%